Analisis Normatif Filosofis terhadap Fatwa Majelis Ulama Indonesia (MUI) tentang Hukum Pengendalian Perubahan Iklim Global - Nasution, Ahmad Yani (Mutawasith: Jurnal Hukum Islam, 2025)
Global climate change threatens human health, socio-economic stability, and environmental sustainability. This study aims to normatively-philosophically analyze the legal construction and scriptural argumentation in the Indonesian Council of Ulama (MUI) Fatwa No. 86 of 2023 on the Law of Global Climate Change Control, as well as to assess its coherence with the principles of maqāṣid al-sharī‘ah and contemporary Islamic environmental ethics. The approach employed is content analysis of the official text of the fatwa as the primary source, supported by books and academic journals on climate change as secondary sources. This research fills a gap in the literature, which has so far tended to highlight the practical fiqhiyyah aspects of MUI environmental fatwas, by offering a philosophical reading of the maqāṣid-based rationality and the istislāḥī–sadd al-dharī‘ah framework used in the formulation of the fatwa. The findings show that MUI Fatwa No. 86 of 2023 affirms the prohibition of environmental destruction and the obligation of climate mitigation and adaptation as part of the protection of life, property, and the preservation of the earth, thereby theoretically enriching the discourse on fiqh al-bi’ah and practically strengthening the normative basis for climate change control movements and policies in Indonesia.